2022
DOI: 10.1186/s12885-022-09988-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter diagnostic model based on 18F-FDG PET and clinical characteristics can differentiate thymic epithelial tumors from thymic lymphomas

Abstract: Objective To evaluate the diagnostic performance of combined multiparametric 18F-fluorodeoxyglucose positron emission tomography (18FDG PET) with clinical characteristics in differentiating thymic epithelial tumors (TETs) from thymic lymphomas. Patients and methods A total of 173 patients with 80 TETs and 93 thymic lymphomas who underwent 18F-FDG PET/CT before treatment were enrolled in this retrospective study. All patients were confirmed by patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Mediastinal lymphomas is predominantly occurred in young adult life [ 25 ]. Previous studies reported that there was a certain value for the age in differentiating TETs and anterior mediastinal lymphomas [ 18 , 26 ]. In this current study, the mean age of patients with invasive TETs was significantly higher than that of anterior mediastinal lymphomas patients (55.84 ± 11.43 years vs 28.97 ± 10.37 years, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mediastinal lymphomas is predominantly occurred in young adult life [ 25 ]. Previous studies reported that there was a certain value for the age in differentiating TETs and anterior mediastinal lymphomas [ 18 , 26 ]. In this current study, the mean age of patients with invasive TETs was significantly higher than that of anterior mediastinal lymphomas patients (55.84 ± 11.43 years vs 28.97 ± 10.37 years, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Giorgio Treglia et al demonstrated that the mean SUVmax in thymic carcinomas was significantly higher than low-risk thymomas [ 30 ]. Moreover, SUVmax also can be used in differentiating TETs and anterior mediastinal lymphomas [ 18 , 31 ]. Catherine T Byrd et al reported that anterior mediastinal tumors with SUVmax less than 7.50 were likely thymoma while anterior mediastinal lymphomas were likely with SUVmax greater than 12.85, and as for tumors with SUVmax between 7.50 and 12.85, it was still need to be biopsied to rule out lymphoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation